FRAMEWORK FORMULATION OF BUSINESS PERFORMANCE IMPROVEMENT FACTORS OF ISO CERTIFIED COMPANIES AND PILOT TESTING OF ITS SURVEY QUESTIONNAIRE IN PAKISTAN (Proceedings of the International Conference on Education, 2023)
A comprehensive literature review was done to extract the world ISO Management System (IMS) standards certifications data from the year 2018 to 2021 which also shows the Pakistan shared in it. Objective: To design a survey questionnaire and its mock and pilot testing for reliability and validity. Research Design and Methodology: The present phase of the mega research study design, formulation and pilot-testing of a survey questionnaire is based on the reviewed Framework of Synthesized Business Performance Improvement Factors of IMS Standards Certification. Based on a synthesized framework of business performance improvement factors, a survey questionnaire is designed and was subjected to extensive mock exercises. Novelty: It can be the only national data survey on ISO certification from all chambers of commerce and industry of Pakistan. Results: The mock testing results confirm a positive relationship between IMS standards certification and business performance improvement. Pilot testing was done in a provincial and federal chamber of commerce and industry to verify its construct reliability and validity. Conclusion: The pilot-tested and validated questionnaire is ready to be used in the national survey for the collection of data from both IMS-certified commercial companies and non-IMS companies Recommendation: To use the national data of IMS-certified and Non-IMS companies for performance comparison. Acknowledgement: HEC Pakistan has funded this research under NRPU project -12084.
Keywords: ISO Management System Standards; Business Performance Improvement Factors/elements; Mock Exercises; Merits of IMS system standards Certification; Benefits; GDP improvement; SDGs attainment